3D-printable alkali-activated concretes for building applications: a critical review - Amran, Mugahed; Abdelgader, Hakim S.; Onaizi, Ali M.; Fediuk, Roman; Ozbakkaloglu, Togay; Rashid, Raizal S.M.; Murali, G. (Elsevier, 2022)
The construction sector has embraced digitalization and industrialization to boost production, reduce material consumption, and improve workmanship. The 3D-printed concrete technology (3DPCT), more broadly recognized as the design of a 3D object via a computer-aided design (CAD) model or a digital 3D model, has accelerated considerable progress in these areas in other industries. Although 3DPCT has advanced remarkably in recent years, producing an appropriate 3D printing material that improves performance while reducing material consumption, which is really important for CO2 reduction, is urgently needed. The present 3DPCT faces many obstacles, one of which is the limited range of printable concretes. To tackle this limitation, extensive studies on developing creative approaches for formulating alkali-activated materials (AAMs) for 3DPCT for modern building applications have been conducted. AAMs are maintainable substitutive binders to ordinary Portland cement. Therefore, the need to undertake a comprehensive literature review on the current status of AAM performance on 3D-printable concretes for building applications is substantial. This article comprehensively reviews the quality requirements, advantages, disadvantages, common techniques, delivery, and placement of 3DCP. This literature also delivers indepth reviews on the behaviors and the properties of AAM-based concrete composites used in 3D-printed construction. Moreover, research trends are moving toward a wide-ranging understanding concerning the economic benefits and the environmental footprints of 3DCP for building applications with AAMs as suitable concrete materials for the emerging robust eco-friendly concrete composite for digital construction constructions nowadays. Given the merits of the study, several hotspot research topics for future investigations are also provided for facilitating the wide use of 3DPCT in real applications to address rapidly the gap between demand and supply for smart and cost-effective homes for upcoming generations.